CRISPR/Cas9 Edition of the F9 Gene in Human Mesenchymal Stem Cells for Hemophilia B Therapy - Irving Jair Lara-Navarro; Luis Felipe Jave-Suárez; Juan Antonio Marchal; Ana Rebeca Jaloma-Cruz (Life)
Hemophilia B is a genetic disorder characterized by clotting factor IX deficiency and bleeding in joints and muscles. Current treatments involve intravenous infusion of plasma-derived products or recombinant proteins, which have limited efficacy due to the short half-life of infused proteins. Recently, gene therapy for bleeding disorders has offered a potential solution. This study aimed to develop an in vitro gene therapy model using the CRISPR/Cas9 system to incorporate the F9 cDNA in human mesenchymal stem cells (hMSCs) to produce clotting factor IX. RNA guide sequences targeting the promoter-exon 1 region of the F9 gene were designed to incorporate a wild-type F9 cDNA into the cells. Knockin was performed with the CRISPR/Cas9 system and pDONOR-CMV/cDNAF9/IRES/EGFP vector template recombination in Lenti-X HEK293 cells and MSCs. A lentiviral F9 cDNA vector was designed as a FIX secretor model to validate the CRISPR/Cas9 system. Results showed successful gene editing and F9 expression in both cell models, although editing efficiency was lower in hMSCs. Future investigations will focus on improving gene editing efficiency using different transfection conditions or hybrid methodologies. This study demonstrates the potential of CRISPR/Cas9-based gene therapy in hMSCs as a target for hemophilia B. Further optimizations are required to translate these findings into clinical applications.